Uji Efektivitas Ekstrak Etanol Herba Krokot (Portulaca Oleracea L) pada Mencit Putih (Mus Musculus) dengan Induksi Asam Asetat - Marissa Aulia; Muhammad Walid (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pain is the body's response to tissue damage that is often addressed using analgesic compounds. Purslane plants (Portulaca oleracea L) are known to contain flavonoids, saponins, tannins, and alkaloids that have potential as analgesics. This study aims to test the analgesic effectiveness of purslane ethanol extract by writhing test method using white mice (Mus musculus) induced by 1% acetic acid. A total of 15 mice were divided into 5 treatment groups, namely negative control, positive control (paracetamol), and three groups with doses of purslane extract 200 mg/kgBB, 400 mg/kgBB, and 800 mg/kgBB. The number of writhes was observed every 15 minutes for 1 hour, and the percentage of protective power was calculated. The results showed that the dose of 800 mg/kgBB gave the highest analgesic effect with a percent protection power of 65.28%, followed by doses of 400 mg/kgBB (52.4%) and 200 mg/kgBB (30.6%). The highest analgesic effect was achieved at a dose of 800 mg/kgBB, almost equivalent to the positive control. This shows the significant potential of purslane ethanol extract as an analgesic agent.